2009
DOI: 10.1016/j.ejcts.2008.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of arterial switch operation with an emphasis on function and dimensions of left ventricle and aorta☆

Abstract: Clinical outcome is good 20 years after arterial switch operation and aortic valve function remains preserved in most patients. However, aortic root dilatation is present in two thirds of patients emphasizing the need for careful follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 22 publications
3
21
1
3
Order By: Relevance
“…One study (Simko & McGinnis, 2003) used the Sickness Impact Profile (SIP) in which significantly lower scores were reported by young adults with CHD in the physical and psychosocial domains compared with healthy matched controls. Dutch youth reported significantly lower scores in vitality, depressive, and aggressive moods on the TNO-AZL questionnaire for Adult's Health-related Quality of Life (TAAQOL) compared with normative data (Vandekerckhove et al, 2009). The type and severity of the heart defect was associated with differing levels of QoL; significantly higher QoL scores were reported by young adults with mild CHD as compared with those with complex CHD (Kamphuis et al, 2004), those with tetralogy of Fallot compared with those with an atrial septal defect (Ternestedt et al, 2001), and men without erectile dysfunction compared with those with erectile dysfunction (within a sample of 332 German men with CHD; Vigl et al, 2009).…”
Section: Qol Of Individuals With Chdmentioning
confidence: 98%
“…One study (Simko & McGinnis, 2003) used the Sickness Impact Profile (SIP) in which significantly lower scores were reported by young adults with CHD in the physical and psychosocial domains compared with healthy matched controls. Dutch youth reported significantly lower scores in vitality, depressive, and aggressive moods on the TNO-AZL questionnaire for Adult's Health-related Quality of Life (TAAQOL) compared with normative data (Vandekerckhove et al, 2009). The type and severity of the heart defect was associated with differing levels of QoL; significantly higher QoL scores were reported by young adults with mild CHD as compared with those with complex CHD (Kamphuis et al, 2004), those with tetralogy of Fallot compared with those with an atrial septal defect (Ternestedt et al, 2001), and men without erectile dysfunction compared with those with erectile dysfunction (within a sample of 332 German men with CHD; Vigl et al, 2009).…”
Section: Qol Of Individuals With Chdmentioning
confidence: 98%
“…They include coronary complications,11–13 right ventricular outflow tract obstruction14–17 and neo-aortic valve regurgitation 18–20. Moreover, neo-aortic dilation is present in the majority of adult patients 21 22. However, little data exist concerning the progression of neo-aortic dilation in adulthood, and it has been suggested neo-aortic dilation will stabilise over time 23.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated data, with reports of the indexed neo-aortic root dimensions progressively increasing over time [17]. Neo-aortic valve regurgitation may also be an important late complication, and although uncommon, the need for aortic valve repair or replacement has now been reported in several series late after ASO [18]. The function of the aortic root, including the pulmonary valve, that has become the new aortic valve, plays a crucial role in the long-term follow-up after the ASO.…”
Section: Discussionmentioning
confidence: 87%